Longer food miles of beef under self-insufficiency and halal requirements - La Ode Nazaruddin; Qisthina Aulia; Mária Fekete-Farkas; Balázs Gyenge (Agriculture & Food Security)
Abstract Background Indonesia encounters self-insufficiency in beef, which domestic needs should be fulfilled from imports, implying longer food miles. This study aims to disclose factors affecting food miles and self-insufficiency of beef in Indonesia. Results First, self-insufficiency of beef is directly affected by urbanisation and consumption behaviour and indirectly affected by urbanisation through the change of consumption behaviour; second, the change in consumption behaviour itself is contributed by rapid urbanisation; third, longer food miles of beef are affected by self-insufficiency (directly), consumption behaviour (directly and indirectly through self-insufficiency), and halal requirements (directly). Conclusion Self-insufficiency is affected by urbanisation and the change in consumption behaviour. Longer food miles of beef are affected by changes in consumption behaviour and self-insufficiency induced by the change in urban consumption behaviour. Longer food miles of beef are tolerable among Indonesian consumers in situations of self-insufficiency, provided that halal requirements are fulfilled. Moreover, this study has some practical implications for consumers, meat traders in Muslim-majority countries, governments in Muslim-majority countries, domestic farmers, business players in meat supply chain in exporting countries, governments in exporting countries, and halal-certifying bodies mainly in Muslim minority countries. The findings from the present study have theoretical contributions to green supply chain and logistics, self-sufficiency and food security, halal food miles, and sustainable development.